Influencia do soerguimento do alto Paranaiba na sedimentacao pos- basaltica na area do Triangulo Mineiro (MG), borda NNE da Bacia do Parana - Barcelos, J. H. (My University, 1989)
Faciologic analysis method was applied to after-basaltic sedimentary deposits in Triangulo Mineiro (MG) area. Faciologic association 1 (Adamantina formation) and unities 1 to 5 (Uberaba formation) are related to the fluvial and lake deposits: faciologic association 3 (Ponte Alta Member) and 2 (Sierra da Galga Member) represent the sedimentary deposits associated to the alluvial fans conditions. With faciologic association and unities it could be to recognize the paleogeografic and tectonic conditions in sedimentation time of that depositional tract. -English summary
Influence of the Alto Paranaiba uplift in post-basaltic sedimentation of the Triangulo Mineiro (MG) area, NNE border of the Parana Basin
Keywords: Adamantina Formation; Cretaceous; lake deposit; sedimentation; tectonics; Uberaba formation; uplift; Brazil, Parana Basin, Triangulo Mineiro area